Retensi Zat Makanan Pada Ayam Kampung yang Mengkonsumsi Ransum Mengandung Tepung Azolla (Azolla microphilla) Difermentasi dengan Jamur Pleurotus ostreatus - Noferdiman Noferdiman; Zubaidah Zubaidah; Sestilawarti Sestilawarti (Fakultas Peternakan Universitas Jambi, 2017)
Abstract This study was aimed to determine the retention of dry matter, nitrogen and crude fiber of Azolla Meal (Azollamicrophilla) fermented with Pleurotus ostreatus mushroom as a mixture of kampung chicken rations. The experimental design used was Completely Randomized Design which consisted of 4 treatments and 5 replicates; P0 (Ration 0% Azolla Meal Fermentation (AF), P1 (Ration containing 5% AF), P2 (Ration containing 10% AF ) and P3 (Ration containing 15% AF). The observed variables were dry matter retention (DM), nitrogen retention (N) and crude fiber digestibility (CF). The data found were analyzed using variance analysis. The evident effect of the treatment on the observed variables then tested by Duncan's multiple range test. The results of the research presented that the use of fermented Azolla starch up to 15% in kampung chicken ration had no significant effect (P> 0,05) on the retention of dry matter, nitrogen and crude fiber. The fermentation of Azolla Meal with Pleurotus ostreatus (AF) mushroom improved the quality of Azolla as feed ingredients up to 15%. This research concluded that the use of fermented Azolla Meal with Pleurotus ostreatus (AF) mushroom in kampung chicken ration up to 15% can be used without affecting the retention of dry matter (DM), nitrogen (N) and crude fiber digestibility (CF). Keywords : Nutrient retention, Azolla Meal Fermentation (AF), and kampung chicken